A mathematical model of PD controller-based DC motor system using system identification approach - Nur Naajihah, Ab Rahman; Nafrizuan, Mat Yahya (Springer, 2023)
A mathematical model is a crucial element of a system. This is to ensure the system obtains outstanding performance, particularly when there is a controller included. Thus, in this study, a comparison between DC motor PD controllers with and without system identification will be made with the concept of poles and zeros. Furthermore, the Cohen-Coon tuning method will be applied to tune the parameters of the proposed controller by using the MATLAB/Simulink software. Then, some tests were performed by varying the number of poles and zeros. After that, the performance of the DC motor with the proposed controller will be assessed in terms of transient response aspects. Throughout the study, it can be guaranteed that the process of system identification is needed to ensure that the performance of the DC motor can be enhanced. With that justification, the performance of the DC motor PD controller with two poles and no zero is better compared to the others. It had the shortest rise time of 0.052 s, the shortest settling time of 1.906 s, the shortest peak time of 1.142 s, and the lowest overshoot of 56.56 percent with no steady-state error.